Prototype of bulk cooking oil scaling machine using flow sensor and infrared sensor based on arduino nano - Nafazi, Muhammad; Muhammad, Muhammad; Multazam, Teuku; Meliala, Selamat; Nasution, Fakhruddin Ahmad (Geuthèë Institute, 2023)
Traditional scales generally make it difficult for some people from the lower middle class to buy oil according to their needs. This price-based bulk oil weighing machine is aimed at the lower middle class, allowing them to buy any amount of oil they want. This innovation is very important in facilitating access and fair transactions in obtaining bulk oil. The aim of this research is to develop a weighing system that is affordable, easy to use, and can provide information regarding the volume, weight of bulk oil and the price to be paid. In developing this weighing machine, the focus was placed on the aspects of ease of use, reliability and affordable cost. This machine is designed to be able to measure volume and weight of bulk oil quite accurately using flow and loadcell sensors. This sensor will convert the received load into an electrical signal that can be processed to produce an accurate weight value